The Effect of Telemedicine on Access to Acute Stroke Care in Texas: The Story of Age Inequalities - Karen C. Albright; Amelia K. Boehme; Michael T. Mullen; Tzu-Ching Wu; Charles C. Branas; James C. Grotta; Sean I. Savitz; Catherine Wolff; Bisakha Sen; Brendan G. Carr (Stroke Research and Treatment)
Background. Ischemic stroke is a time sensitive disease with the effectiveness of treatment decreasing over time. Treatment is more likely to occur at Primary Stroke Centers (PSC); thus rapid access to acute stroke care through stand-alone PSCs or telemedicine (TM) is vital for all Americans. The objective of this study is to determine if disparities exist in access to PSCs or the extended access to acute stroke care provided by TM. Methods. Data from the US Census Bureau and the 2010 Neilson Claritas Demographic Estimation Program, American Hospital Association annual survey, and The Joint Commission list of PSCs and survey response data for all hospitals in the state of Texas were used. Results. Over 64% of block groups had 60-minute ground access to acute stroke care. The odds of a block group having 60-minute access to acute stroke care decreased with age, despite adjustment for sex, race, ethnicity, socioeconomic status, urbanization, and total population. Conclusion. Our survey of Texas hospitals found that as the median age of a block group increased, the odds of having access to acute stroke care decreased.